Mapping Least Cost Transport Corridors for Soybean Exports from Mato Grosso: A Case Study of Logistics from Farm to Port (Global Journal of Human-Social Science, 2024)
Brazil and the US are world s largest soybean exporters and account for more than 80 of the global exports most of which destined to China Hence the producers of both countries compete directly to place their grain in the same market and their logistic costs are essential to their competitiveness For the producers in Mato Grosso MT Brazil s largest producing state and most distant from ports choosing the best route and transport mode materially impacts their competitiveness The farm to port logistics which refers to the inland transportation from the agricultural production point to the exporting shipping port is central to reducing the total logistics costs and depending on the transport mode choice also impacts the environment differently Various studies have evaluated routes or transport modes individually by analysing their impact and some give an insight into the least cost LC choice yet to the best of our knowledge there are none determining the detailed spatial geographic boundaries of the optimum choice transport corridors for each micro geographic location within MT
Keywords: soybeans; transport corridors; competitive- ness; logistics; farm to port; northern Arc